Neighborhood level amenity inventory to support creation of complete neighborhoods - Kloehn, Alexandra (Kansas State University, 2022)
As the city of Greeley grows, some older neighborhoods are experiencing high resident turnover, a lack of care for the community, and an overall decrease in resident wellbeing. When residents like their neighborhood they tend to treat it better. Bai et al. (2020) found that nearness to the metro station and central business district affects resident enjoyment of their community and housing prices. In this project I develop a tool using Google Maps and GIS to inventory Greeley neighborhood’s distance from amenities that are shown to be important components to complete neighborhoods in various scholarly journals. With this research, the city planning team can identify missing resources for struggling neighborhoods and use zoning and economic development strategies to bring those elements to that neighborhood. The tool highlighted neighborhoods with low access to amenities around the outskirts of the community and found that the highest access to amenities is in downtown Greeley and near Highway 34. There appears to be little correlation between known wealth of a neighborhood and access to amenities. A deeper look showed that library access is lacking in the middle of the city and that ethnic grocery stores closed gaps left by lacking mainstream grocery stores. Future research can look at demographic data from these neighborhoods and city comparisons to further predict neighborhood needs.
Keywords: Neighborhood; Amenity; Inventory; Planning; Community gathering space; Complete community